John Henry Newman on truth and its counterfeits : a guide for our times - Hütter, Reinhard, 1958- (Sacra doctrina (Series), 2020)
"Through the thought and writings of John Henry Newman, the author explores four counterfeits of important Christian ideas in secularized culture--conscience, faith, doctrine, and the university--and presents true exemplars of these notions for the modern world"--